2022
DOI: 10.3389/fcvm.2022.986905
|View full text |Cite
|
Sign up to set email alerts
|

β-sitosterol inhibits trimethylamine production by regulating the gut microbiota and attenuates atherosclerosis in ApoE–/– mice

Abstract: The intestinal microbial metabolite trimethylamine (TMA), which is activated by flavin monooxygenase (FMO) to produce trimethylamine-N-oxide (TMAO), has been implicated in the pathogenesis of atherosclerosis (AS), leading to the development of therapeutic strategies for AS. This study aimed to investigate whether β-sitosterol can inhibit TMA production in ApoE–/– mice by reshaping the gut microbial structure. 16S rRNA sequencing of the gut microbiota showed that β-sitosterol has beneficial effects on intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…A study reported the antioxidant, anti-inflammatory, and cardioprotective effects of kaempferol and suggested its potential as a drug candidate for treating and preventing AS ( Chen et al., 2022b ). Beta-sitosterol can effectively reduce the production of the intestinal microbial metabolite trimethylamine to ameliorate atherosclerotic plaques in AS mice ( Wu et al., 2022 ). Stigmasterol activates the nuclear receptor LXR to promote cholesterol secretion via the intestinal tract and inhibits the expression of proinflammatory mediators such as IL-6, IL-1β, COX-2, and TNF-α to ameliorate AS ( Lifsey et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study reported the antioxidant, anti-inflammatory, and cardioprotective effects of kaempferol and suggested its potential as a drug candidate for treating and preventing AS ( Chen et al., 2022b ). Beta-sitosterol can effectively reduce the production of the intestinal microbial metabolite trimethylamine to ameliorate atherosclerotic plaques in AS mice ( Wu et al., 2022 ). Stigmasterol activates the nuclear receptor LXR to promote cholesterol secretion via the intestinal tract and inhibits the expression of proinflammatory mediators such as IL-6, IL-1β, COX-2, and TNF-α to ameliorate AS ( Lifsey et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sitosterol intervention can increase the abundance of Lactobacillus pentosus to produce SCFAs in the gut of mice, 195 contributing to alleviate cognitive impairment through the GBA. 196 Intake of β-sitosterol inhibits TMA production in the gut of mice, 197 leading to a reduction in TMAO levels in the liver, 198 and ultimately lowering the cognitive impairment caused by TMAO. Moreover, stigmasterol activates the butyrate–PPARγ axis, and re-establishes the equilibrium of Treg/Th17 cells to alleviate the damage to the cerebrovascular system caused by the massive release of Th17, and ultimately improves cognition in colitis mice.…”
Section: Dietary Lipids the Gba And Cognitionmentioning
confidence: 99%
“…On the other hand, soyasaponins, which are commonly found in soybean, have been observed to reduce inflammation caused by allergies by positively impacting the composition of the intestinal flora ( Nagano et al., 2017 ). Additionally, other bioactive compounds, like β-sitosterol, a phytosterol commonly present in legume ingredients found in Mediterranean diets ( Jiménez-Escrig et al., 2006 ), have demonstrated the capability to inhibit certain bacterial genera that possess the genes responsible for a major pathway leading to atherosclerosis (the build-up of lipids in arteries) ( Wu et al., 2022 ). Plant sterols have also been associated with an increase in the abundance of Eubacterium hallii ( Cuevas-Tena et al., 2018 ), an anaerobic bacterium currently classified as Anaerobutyricum hallii , known for producing butyrate, which has positive implications for insulin sensitivity treatments in obese and diabetic mice ( Udayappan et al., 2016 ).…”
Section: Soil- and Gut Microbes And Functional Diversity Conceptmentioning
confidence: 99%